If only we knew what we know : the transfer of internal knowledge and best practice - O'Dell, Carla (Free P. New YorkUS, 1998)
Uses case studies to demonstrate how the profitability/effectiveness of an organization can be improved by capturing, transferring, and putting into practical use, internally available knowledge. Provides a model for ensuring that the transferred knowledge accomplishes its purpose. Identifies the 3 components of the model, namely: the 3 value propositions; four enablers; and the four-step change process. Discusses each component in detail.